How is copepod functional diversity shaped by 2015-2016 El Niño and seasonal water masses in a coastal ecosystem of Southwest Atlantic? - Bárbara Santos Menezes; Érica Caroline Becker; Flora Balcão Agnelli; Luis Carlos Pinto de Macedo Soares; Cristina de Oliveira Dias; Andrea Santarosa Freire (Ocean and Coastal Research)
Functional traits, short life cycles, and the pivotal role in the ocean make copepod diversity a solid foundation for assessing the effect of global changes in marine food webs and ecosystem functioning. Climate change and extreme events, particularly El Niño, can affect coastal ecosystems. The Arvoredo Marine Biological Reserve (MPA), located in highly productive coastal waters of the Southern Brazilian Bight, presents complex climate and oceanographic conditions. This study investigates the influence of oceanographic processes and El Niño 2015-2016 on the copepod functional diversity from 2014 to 2016 in the Arvoredo MPA. Horizontal tows were performed using a WP2 net with a mesh size of 200 µm. The 41 species accounted for 19 functional entities and four functional groups. Our findings reveal that the seasonal intrusion of water masses influenced copepod functional diversity. During summer, the upwelling of South Atlantic Central Water increased nutrient availability and favored large herbivore-omnivores and carnivores. The Plata Plume Water enrichment during winter coincided with a decline in functional richness and abundance, leading to the predominance of the Oithona nana, a small-sized omnivore. Compensatory mechanisms were observed as functional equivalence and species composition shifts. Acartia lilljeborgii and Temora turbinata exhibited functional equivalence and compensated for each other in response to salinity changes associated with upwelling and El Niño. The copepod assemblage demonstrated the ability to maintain functional diversity despite changes in copepod abundance. However, the decline in functional diversity and abundance during the intense winter indicated potential disruption in trophic dynamics and ecosystem functioning. Maintaining balance and compensating for disturbances such as El Niño is crucial for marine food web resilience. The functional trait approach provided a comprehensive understanding of the copepod assemblage in Arvoredo MPA, contributing to a broader knowledge of the impact of oceanographic processes intensification. Monitoring functional diversity and abundance is crucial for evaluating the effects of copepod assemblage changes in ecosystem functionings.